The Impact of the Price Earnings Ratio (PER), the Debt to Equity Ratio (DER), and the Dividend Payout Ratio (DPR) on the Price Book Value (PBV) of Trading Companies Listed on the Indonesia Stock Exchange (IDX) from 2015 to 2019 - Hasanudin Hasanudin (Budapest International Research and Critics University, 2022)
PER, DER, and DPR (dividend payout ratios) on Price Book Value (PBV) in Indonesian Stock Exchange-listed trading companies are all examined for the years 2015–2019 in this study (IDX). Secondary data are used in this investigation. Purposive sampling was used to obtain the sample. The results of multiple linear analysis indicate that 1) PER has a positive and statistically significant effect on PBV in trading companies listed on the IDX. (2) DER has a severe negative impact on the PBV of trading companies listed on the IDX. (3) DPR has a major negative influence on the PBV of companies in the trading sector that are listed on the IDX.